Spłakane deszczem... - Krajewska, Anna (Przestrzenie Teorii, 2023)
A text dedicated to the memory of Professor Stanisław Balbus, a member of the Editorial Committee of the journal “Przestrzenie Teorii” [Spaces in Theory].